Avaliação de marcadores bioquímicos, de estresse oxidativo e do efeito antioxidante da quercetina no hipotireoidismo - Santi, Adriana (2014)
Hypothyroidism is characterized by a disorder resulting from deficiency of thyroid hormones and is related to lipid metabolism dysfunction and cardiovascular diseases development risk. However, these changes in hypothyroidism need to be understood. Thus, this study aimed to evaluate the association between lipid, inflammatory and oxidative stress markers in patients with hypothyroidism and antioxidant effects of quercetin in these markers, using hypothyroidism experimental model induced by methimazole in rats. The methodology and results are presented in the form of articles. In article 1, were evaluated the oxidative stress biomarkers in 20 patients with subclinical hypothyroidism (SH) (49.12 ± 10.85 years). Thiobarbituric acid reactive substances (TBARS), superoxide dismutase (SOD), catalase (CAT) and arylesterase (ARE) were analyzed in SH patients and controls. In addition, were measured plasmatic lipids: total cholesterol (TC), triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). TBARS levels and CAT activity were higher in subclinical hypothyroidism patients, such as TC and LDL-C plasmatic levels. Arylesterase activity was lower in the SH group. Correlations were observed between plasmatic lipids and oxidative stress biomarkers and thyroid-stimulating hormone (TSH). TSH was correlated with TBARS, CAT, and SOD. The second study (manuscript 1) aimed to investigate the association between inflammatory biomarkers and overt hypothyroidism (OH). Plasmatic levels of cytokines were determinate: interleukin 1 (IL-1), interleukin 6 (IL- 6), tumor necrosis factor alpha (TNF-α), interferon gamma (INF-ɣ) and the levels of cell free DNA (cf-DNA). Furthermore, we evaluated lipid profile and prothrombotic markers (fibrinogen and D-dimer). OH patients had pro-inflammatory profile, resulted from high levels of cytokines and cf-DNA. Lipids and prothrombotic markers also showed elevated. Significant associations between inflammatory status and lipid profile were observed in hypothyroid patients. Manuscript 2 evaluates the effect of quercetin on oxidative stress biomarkers in methimazole (MMI) - induced hypothyroid rats. Hypothyroidism was induced by administering MMI at 20 mg/100 ml in the drinking water, for 30 days. After this period, rats received orally 10 or 25 mg/kg of quercetin (QT) for 8 weeks. Sixty male wistar rats were randomly divided into six groups (group I, control; group II, QT10; group III, QT25; group IV, hypothyroid; group V, hypothyroid + QT10; group VI, hypothyroid + QT25). Hypothyroid rats showed hepatic, renal and serum TBARS levels increased, along with increased protein carbonyl (PCO) in liver and increased ROS levels in liver and kidney. Quercetin administration (QT10 and 25), was effective in decreasing TBARS levels in serum and kidney, PCO in liver and ROS generation in liver and kidney tissues. Moreover, in hypothyroid group were observed high TBARS levels in cerebral cortex and hippocampus. QT25 treatment decreased the levels in both tissues. Administration of QT25 to hypothyroid rats resulted in decreased SOD activities in liver and whole blood and increased liver CAT activity. Ascorbic acid levels and total oxidative scavenging capacity (TOSC) were increased in liver and kidney rats after QT10 and QT25 treatment. These results suggest association between oxidative stress and hypothyroidism that may potentially modulated by antioxidant supplementation such as quercetin. These findings are of great importance in understanding the biochemical dysfunctions and oxidative status in hypothyroidism, as well as, in research of antioxidants strategies to be used as adjuncts in the treatment of this disorder.